Biphenyl‐Amine‐Based D‐π‐A'‐π‐A Sensitizers for DSSCs: Comparative Photo‐Conversion Efficiency in Iodide/triiodide and Cobalt‐Based Redox Electrolyte and DFT Study. Issue 24 (27th June 2019) - Raikwar, Manish M.; Sonigara, Keval K.; Patil, Dinesh S.; Machhi, Hiren; Soni, Saurabh S.; Sekar, Nagaiyan
Abstract: We have designed and synthesized two dye molecules viz. MMR1 ((E)‐2‐cyano‐3‐(5‐((E)‐1‐cyano‐2‐(4′‐(dimethylamino)‐[1, 1′‐biphenyl]‐4‐yl)vinyl)thiophen‐2‐yl)acrylic acid) and MMR2 (2‐((Z)‐5‐((5‐((E)‐1‐cyano‐2‐(4′‐(dimethylamino)‐[1, 1′‐biphenyl]‐4‐yl)vinyl)thiophen‐2‐yl)methylene)‐4‐oxo‐2‐thioxothiazolidin‐3‐yl)acetic acid) with D‐π‐A'‐π‐A frameworks. The synthesized interfacial modifiers have dimethyl aniline as the donor group whereas cyanoacetic acid and rhodanine‐3‐acetic acid as the major acceptor groups in MMR1 and MMR2 respectively. The photophysical study in solution medium shows red shifted absorption maxima (λmax ) for MMR2 vs MMR1 . However, the molar extinction coefficient (ϵmax ) for MMR2 is found to be lower than MMR1 . The photovoltaic characterization of these molecules was carried out using iodide/triiodide and cobalt (II/III) based redox electrolytes for comparision. The molecules showed improved efficiency with the cobalt based electrolytes where MMR1 showed the highest power conversion efficiency (PCE) of 3.25% ( Jsc =7.28 mA/cm 2, Voc =0.713 V, FF =0.63). Further to have a deep insight into these synthesized molecules DFT studies were performed. The polarizability and hyperpolarizability values for the interfacial modifiers are calculated using DFT computation and are found to be correlated to the PCE. Abstract : Two sensitizers MMR1 and MMR2 were synthesized and explored for their DSSC efficiency and NLO responses. Iodine and cobalt based electrolytes were employed to study the power conversation efficiency of the fabricated device. MMR1 showed the highest PCE in both the electrolytes compared to MMR2. The NLO parameters obtained by computational method was also highest for MMR1 which suggest a correlation between the hyperpolarizability values and PCE.